การวิเคราะห์ระบบสายดินเพื่อความปลอดภัยในโรงงานผลิตและบรรจุก๊าซ (ANALYSIS OF GROUNDING SYSTEM FOR SAFETY IN GAS PRODUCTION AND GAS FILLING PLANT) - ชาวหลวง, มณีนุช; แสนโภชน์, พีระยศ; กนกบรรณกร, วีรวุฒิ (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2017)
งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาและวิเคราะห์ระบบรากสายดินของโรงงานอุตสาหกรรมผลิตและบรรจุก๊าซ เพื่อใช้เป็นแนวทางในการปรับปรุงระบบรากสายดินให้เป็นไปตามข้อกำหนดทางวิศวกรรมความปลอดภัยในอุตสาหกรรมผลิตและบรรจุก๊าซจะออกแบบและติดตั้งระบบรากสายดินให้เป็นไปตามมาตรฐาน BS Std 7671-2008 (BS 7671:2008) และมาตรฐาน IEEE Std 142-2007 (IEEE 142:2007) ซึ่งมีความแตกต่างจากข้อกำหนดของมาตรฐานการติดตั้งทางไฟฟ้าสำหรับประเทศไทย พ.ศ. 2556 (วสท. 2001-56) จากการสำรวจขนาดสายดินและการวัดค่าความต้านทานดิน จำนวน 24 จุด พบว่า (1) การวิเคราะห์ค่าความต้านทานดิน โดยเทียบกับข้อกำหนดของพื้นที่ที่ทำการศึกษา (กำหนดไม่เกิน 3 โอห์ม), วสท. 2001-56 (กำหนดไม่เกิน 5 โอห์ม), IEEE 142-2007 (กำหนด 1-5 โอห์ม) มีจุดที่ไม่ผ่านเกณฑ์มาตรฐานเป็น 3 จุด, 0 จุด และ 0 จุดตามลำดับ จึงเสนอแนะให้ทำการปักหลักดินเป็นแท่งเหล็กหุ้มทองแดงขนาดเส้นผ่านศูนย์กลาง 15.88 มิลลิเมตร และยาว 3.00 เมตรเพิ่มจำนวน 1 หลักโดยปักขนานกับหลักเดิมจะทำให้ค่าความต้านทานดิน ลดลงจาก 4.90 โอห์มเป็น 2.84 โอห์ม (2) การวิเคราะห์ขนาดสายดินของบริภัณฑ์ไฟฟ้าโดยเทียบกับ BS 7671:2008 และ วสท. 2001-56 พบว่ามีจุดไม่ผ่านมาตรฐาน BS 7671:2008 และ วสท. 2001-56 ทั้งหมด 8 จุด จึงเสนอแนะให้เพิ่มขนาดสายดินของบริภัณฑ์ให้มีขนาดตามมาตรฐานที่กำหนดไว้ โดยต้องคำนึงถึงค่า Earth Fault Loop Impedance ต้องไม่เกินค่าสูงสุดตามที่มาตรฐานกำหนด จึงจะถือว่าขนาดสายดินนั้นมีความเหมาะสม ซึ่งเมื่อตรวจสอบแล้ว โดยเลือกขนาดสายดินตามมาตรฐาน BS 7671:2008 มี 1 จุด ที่ต้องเพิ่มขนาดสายดิน จาก 95 ตร.มม. เป็น 120 ตร.มม. ในขณะที่เลือกขนาดสายดินตามมาตรฐาน วสท. 2001-56 มี 3 จุด ที่ต้องเพิ่มขนาดสายดินจาก 25, 25, และ 25 ตร.มม. เป็น 50, 95, และ 120 ตร.มม. ตามลำดับ (3) การวิเคราะห์ขนาดสายต่อหลักดิน พบว่าทุกจุดผ่านมาตรฐาน BS 7671:2008 และ วสท. 2001-56 จึงไม่ต้องเสนอแนะข้อปรับปรุง (4) การวิเคราะห์การต่อฝาก พบว่ามีบางตำแหน่งที่การต่อฝากที่บริภัณฑ์ประธานสมบูรณ์สอดคล้องกับมาตรฐานแต่การต่อฝากของบริภัณฑ์ไฟฟ้ายังมีบางตำแหน่งไม่สอดคล้องกับมาตรฐาน คำสำคัญ: ระบบรากสายดิน โรงงานผลิตและบรรจุก๊าซ The objective of this research is study and analysis of grounding system for safety in gas production and gas filling plant for improving on safety engineering principles. In gas production and gas filling business were design and installation of grounding system according to BS Std 7671-2008 (BS 7671:2008) and IEEE Std 142-2007 (IEEE 142:2007). There are different from the requirements of Thai Electrical Code 2013 (EIT 2001-56). From the survey and grounding resistance measurement sampling total 24 points. The result was shown : (1) analysis of grounding resistance giving compliance with area study' requirements (not exceed 3 ohms), EIT 2001-56 (not exceed 5 ohms), IEEE 142:2007 (1-5 ohms) found that not compliance with the standard was 3 points, 0 point and 0 point. respectively. The suggestion is adding a second ground rod which is copper-clad steel in 3.00 m long by 15.88 mm diameter rod. By the second ground rod is connected to the single ground rod in parallel yield. There are multiple rod is provided to low grounding resistance from 4.90 ohms to 2.84 ohms. (2) analysis of equipment grounding conductor sizing compared between BS 7671:2008 and EIT 2001-56. The result was found that not compliance with both standard were 8 points. The suggestion is consider to increase a size of equipment grounding conductor shall be calculated to ensure values of grounding fault loop impedance not greater than maximum values of grounding fault loop impedance that can be used. By follow BS7671:2008 the result was shown 1 point to changed a size of equipment grounding conductor from 95 sq.mm to 120 sq.mm. Meanwhile, by follow EIT 2001-56 the result were shown 3 points to change a size of equipment grounding conductor from 25, 25 sq.mm to 50, 95, 120 sq.mm, respectively. (3) analysis of grounding electrode conductor sizing found that were accepted as BS7671:2008 and EIT 2001-56 Std. so this chapter is not a recommendation to improve. (4) analysis of bonding jumper found that the main bonding jumper are bonds as being completely but some positions of equipment bonding jumper are not compliance with standard. Keywords: Grounding System, Gas Production and Gas Filling Plant